The dimensions formation development of the human between religion and science - Ahmed Ali, Ahmed El-Mogtaba Bannga (2003)
The question of the formation and development creation of the human occupies a high place in both religious and scientific theorizing. Through following the journey of the Qur'an and the Sunnah of the Prophet, as the basic sources of thinking about the formation and development creation of the human, we observe that the dimensions of this question started to crystallize in the comprehensive definition of the stages of the formation of the human embryo starting by the meeting of the couple (the meeting of the sperm and the egg): (نُطْفًة), a clot (عَلَقَة). a chewed morsel-size and shaped piece (مُضْغَة), bones (عٍظَام), a unique form (خَلْقاًآخَر), and lastly a complete human(بَشَراً سَوٍيَّاً).